2015
DOI: 10.3389/fpls.2015.00353
|View full text |Cite
|
Sign up to set email alerts
|

Variable content and distribution of arabinogalactan proteins in banana (Musa spp.) under low temperature stress

Abstract: Information on the spatial distribution of arabinogalactan proteins (AGPs) in plant organs and tissues during plant reactions to low temperature (LT) is limited. In this study, the extracellular distribution of AGPs in banana leaves and roots, and their changes under LT stress were investigated in two genotypes differing in chilling tolerance, by immuno-techniques using 17 monoclonal antibodies against different AGP epitopes. Changes in total classical AGPs in banana leaves were also tested. The results showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 63 publications
4
32
0
Order By: Relevance
“…In addition, similar set of antibodies were used to investigate the distribution of their epitopes in banana roots, somatic embryos and leaves. The results showed that some epitopes, such as those recognized by JIM11, JIM13, JIM16, JIM20, LM2 and LM14 appeared in both roots and leaves, but some others, such as JIM4 and MAC204 binding AGPs, were differentially expressed in roots or leaves 27 28 39 . This indicated that AGPs are organ specific.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, similar set of antibodies were used to investigate the distribution of their epitopes in banana roots, somatic embryos and leaves. The results showed that some epitopes, such as those recognized by JIM11, JIM13, JIM16, JIM20, LM2 and LM14 appeared in both roots and leaves, but some others, such as JIM4 and MAC204 binding AGPs, were differentially expressed in roots or leaves 27 28 39 . This indicated that AGPs are organ specific.…”
Section: Discussionmentioning
confidence: 98%
“…AGP and extensin recognizing antibodies used for immunofluorescence labelling were the same as in Yan et al . 39 and Xie et al . 10 respectively.…”
Section: Methodsmentioning
confidence: 93%
“…Despite many studies on the role of AGP in plant development, our understanding of their role in the reaction of the plant to temperature stress is still quite limited. Recent studies have shown that temperature stress strongly affects the distribution and content of AGP in the stigma and ovule of Solanum lycopersicum as well as in banana leaves and roots, which may indicate that AGP are differentially regulated in the response to temperature stress and that their expression and distribution is tissue specific [16,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Banana fruit quality is determined by development and postharvest ripening processes and it plays an important role in the commodity economy (Raza et al, 2016 ). Also, banana production is often threatened by various environmental stresses such as low temperature, drought, salt damage, and various diseases (Ravi et al, 2013 ; Yan et al, 2015 ; Yang et al, 2015 ; Raza et al, 2016 ). Thus, it is necessary to study the molecular mechanism underlying banana fruit development, postharvest ripening, and response to various abiotic stresses.…”
Section: Introductionmentioning
confidence: 99%